Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik Untuk Meningkatkan Kinerja Karyawan Le Grande Hotel - Krismawan, I Made Dwitya; Susila, I Made Gede Darma; Suriyani, Ni Nyoman Ayu (Jurnal Mosaik Hospitaliti, 2022)
The objective of this study is firstly to find out the intrinsic motivation affecting the performance of hotel employees, secondly to find out the intrinsic motivation affecting the performance of hotel employees, and thirdly to find out both intrinsic and extrinsic motivations that hotel employees The performance of affects the performance of hotel employees. Find out the percent effect of intrinsic motivation and extrinsic motivation on restaurant and employee performance. Data were obtained through observations, interviews and questionnaires administered to 52 Grand Hotel employees. This study adopts a quantitative method, i.e. uses questionnaire data to process the outcome data, and uses SPSS version 23 software for the analysis. Research results show that on the performance of (X1). There is a positive effect, with a β coefficient value of 0.393 K, which is positive, and a significance value of 0.003. (X2) has a positive effect on performance, with a β coefficient value of 0.362, which is positive and significant at 0.000. The percentage effect of both intrinsic motivation and extrinsic motivation on employee performance is greater than 67.9%. It is hoped that companies can fulfill their responsibilities to improve employee performance, one of which is to provide employees with the best motivation to work.